MITOLOGI POLA TIGA PADA PROSESI TRADISI NGAROT DESA JAMBAK KECAMATAN CIKEDUNG KABUPATEN INDRAMAYU - Irmawati Irmawati (LPPM STAIS Dharma Indramayu, 2021)
This research is entitled The Mythology of Three Patterns in theTradition Ngarot of Jambak Village, Indramayu Regency, which aims to describe and analyze the Three Patterns of the Ngarot tradition procession in Jambak Village. To explore the data, using descriptive analysis method with a qualitative approach assisted by interview techniques, observation, literature study, and documentation, then the data is reduced, displayed, analyzed and verified. The findings of the research show that: The tradition Ngarot has the aim of fostering healthy relationships, so that young people get to know each other, adjust each other's attitudes, desires and noble behavior in accordance with eastern cultural values. Ngarot is one of the methods or ways to mobilize and foster a sense of unity and integrity among young people before starting to cultivate and plant rice. In the tradition Ngarot there are meanings, symbols or patterns in its implementation. However, rarely do people understand the meanings, symbols or patterns contained in the tradition Ngarot. The traditional ritual Ngarot in Jambak village is the Triple Pattern. Where in the order of the parade starting from the residence of the Village Head, going around the parade to the village boundary then returning to the Great Mosque and ending at the Village Hall. Ngarot traditional procession in Jambak village has local wisdom values ​​and icons for the Jambak village community, including: religious, social, educational, artistic and language values. The results of this study are expected to be useful for developing community appreciation of the living traditions of the local community and disseminating the concept of local wisdom values ​​through academic and community education. Other hopes can contribute as a repertoire to the world of education and to enrich Indonesian cultural treasures.